Contributo para um Modelo de Balcão Único Online: O Caso da Gestão Municipal de Processos Urbanísticos - Tiago Manuel Carvalho de Oliveira Freire (2019)
This project in the field of Information Science, area of Information Management, aims to contribute to the optimization of municipal services, improving the interaction with the citizen and providing public services through digital platforms. It has as context the urbanistic management operations processes and info-communicational flows, focusing the Municipal One-Stop Shop and the opportunity/need to improve a document management and workflow software product, developed by the project host enterprise - IPBRICK, S.A. -, underlining the technological component that underpins the constitution and management of an Active and Permanent Information System (SI-AP). Due to the trans and interdisciplinarity nature of this approach it was essential to analyse the literature about this theme, particularly in the domains of the Public Administration, Processes Management and Engineering and Information Management. At the operational level, the processes of urbanistic operations and their configuration in the iPortalDoc Light software were identified and studied. It was also done a comparative analysis of Municipal One-Stop Shop implementation cases, either supported by this software or others. From the perspective of the infocommunicational flow, the focus was placed on the municipal attendance service phase (reception, capture / production and information flow), as well as on the analysis and modelling of the related organizational processes, taking into account the specificity of the involved mediations: the InfoComunicacional, the Administrative and the Technological (MICAT). The main result is a Municipal Online One-Shop Stop Model proposal, sustained by the digital platform iPortalDoc Light, which configures the mediations underlined in the framework of the municipal services / citizen interactions, according to the legal and regulatory context in force